Phenology of grassland plants responds to urbanization - Tina Christmann; Ingo Kowarik; Maud Bernard-Verdier; Sascha Buchholz; Anne Hiller; Birgit Seitz; Moritz von der Lippe (Urban Ecosystems, 2023)
Understanding phenological responses of plants to changing temperatures is important because of multiple associated ecological consequences. Cities with their urban heat island can be used as laboratories to study phenological adaptation to climate change. However, previous phenology studies focused on trees and did not disentangle the role of micro-climate and urban structures. We studied reproductive phenology of dry grassland species in response to micro-climate and urbanization in Berlin, Germany. Phenological stages were recorded weekly at the individual plant level for five native grassland species across 30 dry grassland sites along an urbanization and temperature gradient. We estimated 50% onset probabilities for flowering and seed maturation of populations, and analysed variation in onset dates using regression models. Early flowering species significantly advanced flowering phenology with increasing mean air temperature but were little influenced by urbanization. By contrast, late-flowering species showed significant phenological responses to both air temperature and urbanization, possibly because micro-climate was most affected by urbanization in late summer. Surprisingly, not all grassland species showed an advanced phenology with increasing intensity of urbanization. This contradicts observed patterns for urban trees, indicating that phenological shifts in urban areas cannot be generalized from the observation of one growth form or taxonomic group. Growth form appears as a possible determinant of phenological responses. Results suggest that the phenology of dry grassland species may directly respond to the urban heat island, albeit with variable direction and magnitude. This has implications for ecosystem services, shifted allergy seasons, changes of biogeochemical cycles and potential ecological mismatches.